Upaya berkelanjutan: peningkatan pupuk kompos plus berbasis limbah nilam dan abu sekam padi di Gampong Teungoh Geunteut, Aceh Besar (Sustainable efforts: enhancing compost plus fertilizer based on patchouli waste and rice husk ash in Teungoh Geunteut Village, Aceh Besar) - Bashair, Fathul; Rida, Muhammad Rasyid; Idrus, Nabila Fardina; Malau, Anisa; Aprilia, Sri; Umam, Muhammad Khalil (Universitas Syiah Kuala, 2023)
Teungoh Geunteut Village is one of the enormous patchouli cultivation centers in Aceh. The high quality of the patchouli oil produced creates great potential for the community to carry out agriculture. However, the large number of patchouli farmers in Teungoh Geunteut Village has resulted in a massive accumulation of patchouli waste thrown out from distillation using steam boilers. The patchouli waste has not yet been utilized properly, resulting in environmental problems. To overcome the uncontrolled accumulation of patchouli waste, PKM-PM teams took the initiative to utilize the patchouli waste into compost plus fertilizer. Compost plus fertilizer can overcome environmental problems and be an alternative solution to replace the undersupply of subsidized fertilizer the government provides. Producing compost plus fertilizer can be enhanced by adding bio silica from rice husk ash. Bio silica contained in rice husk ash has an important role in absorbing the nutrients plants need to initiate quality compost plus fertilizer. The service activities were carried out in August-September 2023 in Teungoh Genteut Village on one of the residents' lands. In carrying out this activity, the team carried out 3 series of stages, namely: (1) socialization on making compost plus fertilizer, (2) direct practice on making solid and liquid compost plus fertilizer, and (3) packaging compost plus fertilizer. The results achieved in this activity are solid and liquid compost fertilizer products that can be used as commercial materials to improve the economy of the Teungoh Geunteut community. Apart from that, this service activity can be used as a forum to increase residents' knowledge and understanding regarding the processing of agricultural waste into compost and techniques for marketing strategies.